Edukasi Pola Hidup Sehat dan Pemeriksaan Kesehatan Gratis sebagai Upaya Peningkatan Kesadaran Kesehatan Masyarakat Desa - Anjur Perkasa Alam; Diyan Yusri; Adinda Putri; Ahmad Sauqi Nasution; Ainul Umami Ernaz; Deni Syahputra; Dinda Wirandika Harahap; Intan Amalia; Jelita Taherani; Jeyssika Armaya; Maulida Yani Husna; M. Ariq Yazid; Merisa Nazlia; Muhammad Ihsan Amali; Poppy Meilinda; Umi Kalsum Cholia Manja Siregar; Zulfadli Maha (Jurnal Kabar Masyarakat, 2026)
Public awareness of the importance of health is still relatively low, especially in rural areas. This is due to limited access to information and health services. This community service activity aims to increase the knowledge and awareness of the village community through healthy lifestyle education and free health checkups. The methods used include counseling, interactive discussions, and health checks including blood pressure, blood sugar, and body mass index. The results of the activity show that there is an increase in public knowledge about a healthy lifestyle and an increase in awareness to carry out regular health check-ups. This activity also has a positive impact in early detection of public health conditions. In addition, the active participation of the community during the activity shows high enthusiasm for the program implemented. This program also strengthens the relationship between health workers and the community in promotive and preventive efforts. Thus, education and free health services are effective strategies in improving the health status of the village community and encouraging the formation of healthy living behaviors in a sustainable and independent manner.